Plastic zone evolution near a crack tip and its role in environmentally assisted cracking - Jesús Toribio; Viktor Kharin (Fracture and Structural Integrity)
This paper analyzes the effects of crack tip plastic strains and compressive residual stresses, created by fatigue pre-cracking, on environmentally assisted cracking of pearlitic steel subjected to localized anodic dissolution and hydrogen assisted fracture. In both situations, cyclic crack tip plasticity improves the behavior of the steel. In the respective cases, the effects are supposed to be due to accelerated local anodic dissolution of the cyclic plastic zone (producing chemical crack blunting) or to the delay of hydrogen entry into the metal caused by residual compressive stresses, thus increasing the fracture load in aggressive environment.